2021
DOI: 10.1002/celc.202100811
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progresses in Carbon Counter Electrode Materials for Perovskite Solar Cells and Modules

Abstract: Though perovskite solar cells (PSCs) or modules (PSMs) are being developed at an unprecedented speed, several obstacles remain to their commercialization. One of the difficult problems is the expensive and unstable Au and Ag counter electrode. Therefore, highly effective, stable, and low‐cost counter electrode materials should be explored. Among various counter electrode materials, carbon is one of the most promising substitutes for their rich sources, low cost, outstanding electrochemical performance, and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…It is inevitable to explore new low-cost electrode materials to replace traditional noble metal electrodes (Au and Ag) for a higher performance-price ratio [215,216]. Carbon materials are ideal candidates because they have similar functions and fine electrical conductivity to Au and can be prepared by silk-screen printing [217]. Lee et al [218] reported that trifluoromethanesulfonic acid (TFMS) vapor doping of the free-standing carbon nanotube (CNT) sheet enabled the tuning of conductivity and work function of the CNT electrode.…”
Section: Electrodementioning
confidence: 99%
“…It is inevitable to explore new low-cost electrode materials to replace traditional noble metal electrodes (Au and Ag) for a higher performance-price ratio [215,216]. Carbon materials are ideal candidates because they have similar functions and fine electrical conductivity to Au and can be prepared by silk-screen printing [217]. Lee et al [218] reported that trifluoromethanesulfonic acid (TFMS) vapor doping of the free-standing carbon nanotube (CNT) sheet enabled the tuning of conductivity and work function of the CNT electrode.…”
Section: Electrodementioning
confidence: 99%
“…84 Extensive efforts on carbon counter electrodes have been made to study their impacts on device efficiency and stability, and details of the development of carbon electrodes can be found in previous reviews. 85,86 Here we only summarize some representative work on carbon electrodes in terms of device architecture, material composition, stability and scalable fabrication. Generally, carbon electrodes are mainly applied in two types of device architectures, including monolithic and conventional layered structures.…”
Section: Carbonmentioning
confidence: 99%
“…25 The combination of transition metal oxides and carbon materials in the CEs of DSSCs can provide total advantages such that the CEs of DSSCs not only have good catalytic reduction ability but also have the characteristics of low intrinsic resistance. 26,27 At present, the combination of transition metal oxides and carbon materials for efficient catalytic electrode materials has attracted extensive attention from researchers. For example, Cheng et al reported the activity and selectivity of nitrogen-doped carbon nanotubes (N-CNT) to transition metal oxide (MOx, where M = Fe, Ni, and Co) nanoclusters for CO 2 RR and achieved a CO yield of 2.6-2.8 mmol cm −2 min −1 at an overpotential of −0.55 V, which is four times higher than that of pristine N-CNT.…”
Section: Introductionmentioning
confidence: 99%